PENGARUH CAMPURAN JENIS KAYU TERHADAP SIFAT VENIR LAMINA (Effect of wood species cominations on laminated veneer properties) - I M Sulastiningsih; Rodjak Memed; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1993)
experimental laminated veneer ( 5 - ply ) were made from 12 wood species veneers glued with urea formaldehyde. Thickness of veneer was 1.5 mm and the range of veneer density was 0.38 - 0.83 g/cm3. Veneers were divided into 3 groups based on their densily i.e. low, medium and high. The laminated veneer properties were tested in accordance with the plywood standards ( JAS and ASTM) the properties tested were density,moisture content, bending strength, tensile strength, compression strength , and moisture resistant. Bonding strengththe results showed that all kinds of wood species combination could be made for laminated veneer glued with urea formaldehyde without any difficullty. The density of laminated veneer was higher than an average veneer density of single. wood species or an average veneer density of mixed wood species. The mechanical properties of laminated veneer increased as the densily of laminated veneer increased and the relationship could be expressed by linear regression equations. As a result, some laminated veneer properties could be estimated from its density without considering its wood species.